The theme of slavery in three Jamaican novels - Pokorná, Karolina (2007)
This B.A. thesis deals with the impact of slavery as depicted in three Jamaican novels, namely in Black Albino by Namba Roy, Banana Bottom by Claude McKay and Abeng by Michelle Cliff.